Piezoelectric biosensors for biorecognition analysis - Encarnacao, Joao M. (2015)
In this work three piezoelectric sensors modified with anti-HIV-1 Vif (virion infectivity factor) single fragment antibodies (4BL scFV), single domains (VH) and camelized single domains (VHD) were constructed and used to detect HIV1 Vif in liquid samples.